Time remaining:
i cant figure this trig question out.

Algebra
Tutor: None Selected Time limit: 1 Day

g(x)=abs(-3x-1)

Sep 23rd, 2014

g(x) = abs (-3x-1) = |-3x-1|

This means g(x) = -3x-1 if -3x-1 is positive i.e if -3x>1 or if x < -1/3

or 

g(x) =-(-3x-1) = 3x+1 if -3x-1 is negative i.e -3x<1 or x > -1/3

Observe that inequality is reversed when we divide by a negative number

Sep 23rd, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Sep 23rd, 2014
...
Sep 23rd, 2014
Dec 10th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer